Faith in the family : a lived religious history of English Catholicism, 1945-82 - Harris, Alana, 1973- (Manchester University Press, 2013)
Drawing upon a multi-disciplinary methodology employing diverse written sources, material practices and vivid life histories, 'Faith in the Family' seeks to assess the impact of the Second Vatican Council on the ordinary believer, alongside contemporaneous shifts in British society relating to social mobility, the sixties, sexual morality and secularisation.